Implementasi Metode Pembelajaran Berbasis Proyek dalam Pendidikan Tinggi untuk Memfasilitasi Pemecahan Masalah Multidisiplin - Ilham Kamaruddin; Mike Nurmalia Sari; Jedithjah Naapia Tamedi Papia; Patima M.Usman; Nining Andriani; Meike Negawati Kesek (Departement of Mathematics Education, 2024)
Project-Based Learning (PBL) has emerged as a prominent approach in higher education to facilitate multidisciplinary problem-solving skills among students. This article explores the implementation of PBL in higher education settings and its effectiveness in fostering collaborative learning and interdisciplinary problem-solving abilities. It discusses the challenges faced in implementing PBL, such as paradigm shifts in teaching roles, logistical issues, and disparities in student readiness and motivation. Effective strategies to address these challenges, including faculty training, resource allocation, and student support, are also discussed. The discussion underscores the potential of PBL to enhance student learning experiences and prepare them for the complexities of the modern workforce.